Inherited Fibrinogen Abnormality Causing Thrombophilia - Egeberg, O (Thrombosis and Haemostasis, 1967)
A family with high incidence of thrombo-embolic diseases is described. Thromboses are reported from members of 3 generations, mostly as leg vein affections, frequently complicated with pulmonal embolism. The family is also known for epileptic manifestations.Investigations of affected members gave normal values for ordinary coagulation tests; procoagulant factor activities were found normal, and no systematic deficiencies in natural anticoagulants could be demonstrated. A tendency to short plasma thrombin times was, however, revealed. The difference between patients and normals could not be eliminated by Al(OH)3-adsorption of the plasmas, and it was still distinct when the plasmas were diluted in defibrinated normal plasma or in congenitally fibrinogen deficient plasma. Isolated fibrinogen from one of the patients gave markedly shortened thrombin times compared with normal fibrinogen. When test plasmas were heat-defibrinated and isolated normal fibrinogen added, no systematic differences in thrombin times between patients and normals could be found, while corresponding addition of patient’s fibrinogen gave shorter thrombin times.The results strongly support the explanation that the plasmas of the affected family members contain an abnormal fibrinogen, and that this protein defect is responsible for their thrombotic tendency.The possibility is considered that the epileptic manifestations in the family might also to some degree be precipitated by cerebral damage due to thrombo-embolic episodes.The coagulation defect seems to be inherited as an autosomal dominant trait.